The Impact of Distance Learning on Academic and Emotional Aspects of Primary School Children - Capodieci, Agnese; Galvani, Stefania; Nobili, Lino; Ramenghi, Luca A.; Uccella, Sara (Advances in Social Sciences Research Journal, 2023)
To reduce the COVID-19 spread, people have been forced to reduce social interactions and this strategy has also been applied to the school world. Italian schools were closed from February to early June 2020 (and, also, thereafter), and distance learning (DL) was adopted to maintain the teaching process. Concerns about consequences for students’ learning and affective wellbeing have been risen. In the hypothesis that DL may have influenced students’ learning, we conducted, starting from November 2020 a screening for learning, reading, writing, and calculating skills in children from grade 1st to 3rd grade, to detect any differences between their performance and normative data. Moreover, a survey was carried out on adults (parents and teachers) close to the children involved in the research, to verify whether the experience of the lockdown may have caused emotional and behavioral changes through a questionnaire addressed to parents and teachers. From the analysis of the results, a general lack of performance in the writing tests emerged, with lower performances in children attending second and third-grade classes. Moreover, a consistent prevalence of children’ malaise was observed by adults close to them during the second pandemic wave, with behavioral manifestations seen by the 69.5% of teachers and by the 54.1% of parents.